A retinal contribution to chronic opioid-induced sleep/wake dysfunction - Bergum, Nikolas, author; Vigh, Jozsef, advisor; Myers, Brent, committee member; Hentges, Shane, committee member; Chanda, Soham, committee member (Colorado State University. Libraries, 2023)
Light is among the most important environmental factors that regulate mammalian sleep/circadian behaviors. Melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs) transmit environmental light information to key sleep/circadian centers in the brain through a process known as photoentrainment. Interestingly, past studies have revealed that ipRGCs express µ-opioid receptors (MORs), the primary molecular target for opioid analgesics. Furthermore, MOR agonists can directly inhibit ipRGC firing. Therefore, we hypothesize that opioid drugs acting on MORs expressed by ipRGCs could disrupt ipRGC-mediated regulation sleep/wake rhythms in response to environmental light/dark cycles. To test this idea, we need to confirm that morphine reaches the mouse retina following systemic delivery. To accomplish this, tissue (retina, brain and serum) was collected from mice following intraperitoneal morphine administration. Importantly, results from this study show that systemically administered morphine selectively accumulates in the mouse retina, but not the serum or the brain. To test the role that MORs expressed by ipRGCs play in opioid-induced dysregulation of sleep/circadian behaviors, we used mini-telemetry devices to assess how chronic morphine alters their sleep/wake behavior in mice. Importantly, we performed these experiments in wildtype mice along with mice lacking MORs exclusively in ipRGCs (McKO). Results from these studies reveal that McKO animals exhibit decreased morphine-induced locomotion compared to controls, which implicates MORs expressed by ipRGCs as a mediator of opioid-induced sleep-wake alterations. Finally, we tested whether ipRGCs developed cellular tolerance to MOR agonists following chronic exposure to morphine. The lack of cellular tolerance development at the level of solitary ipRGCs provides a potential cellular correlate for the persistent sleep/wake dysfunction commonly attributed to chronic opioid exposure. Taken together, these findings support the idea that opioid accumulation in the eye persistently activate MORs on ipRGCs, continuously altering the ability of ipRGCs to transmit light information to the brain's sleep/wake circuitry. This alteration in photic input to the brain could underlie some of the sleep/wake problems associated with long-term opioid use.
Keywords: pharmacology; retina; µ-opioid receptor; photoentrainment; opioids; sleep/wake